Porotrichum squarrosum (Arzeni) H.A. Crum & Steere a new record to Brazil - Peralta, Denilson Fernandes (2021)
Porotrichum squarrosum has never been reported from Brazil and it is a new record. While revising herbarium specimens we found a specimen named Pireella squarrosa (currently  Porotrichum), identified by Massimo Mastracci. We have compared this specimen with records from literature and several hundreds of specimens and found that among specimens previously determined as P. substriatum several belong to P. squarrosum. These taxa are a quite common in Brazil ranging from Amazon, Atlantic Forest to Cerrado phytogeographical domains at elevations from near sea level to about 600 m. These taxa are fast differentiated by the squarrose leaves, spur costa at back and absence of stem central strand in P. squarrosum against to complanate leaves, without spurowed costa at back and presence of central strand in P. substriatum.